Family environment moderates the relation of sluggish cognitive tempo to attention-deficit/hyperactivity disorder inattention and depression - Fredrick, Joseph W. (J Clin Psychol, 2018)
OBJECTIVES: The present study investigated whether a maladaptive family environment would moderate the strength of the relations of Sluggish Cognitive Tempo (SCT) to attention-deficit/hyperactivity disorder inattention (ADHD-IN) and to depressive symptoms in a large sample of college students. METHOD: Participants (N = 3,172), between the ages of 18 to 29 (M±SD(age) = 19.24±1.52; 69.8% women; 80.4% White) and enrolled in five universities in the United States completed self-report measures of symptomatology, interparental conflict, and family expressiveness of emotions. RESULTS: A negative emotional climate strengthened relations of SCT with ADHD-IN and depressive symptoms. Moreover, the lack of a positive emotional climate strengthened the co-occurrence of SCT with depressive symptoms, though not with ADHD-IN. CONCLUSIONS: The present study is the first to demonstrate that the family environment moderates the association between SCT and co-occurring symptomatology in young adults.